2009
DOI: 10.1002/jgm.1296
|View full text |Cite
|
Sign up to set email alerts
|

Use of internally nuclease‐protected single‐strand DNA oligonucleotides and silencing of the mismatch repair protein, MSH2, enhances the replication of corrected cells following gene editing

Abstract: Background Gene editing is potentially a powerful technology for introducing genetic changes by using short single-stranded DNA oligonucleotides (ssODNs). However, their efficiency is reduced by the mismatch repair system, especially MSH2, which may suppress gene editing, although findings vary depending on readout and type of oligonucleotide used. Additionally, successfully edited cells are reported to arrest at the S-or G2-phase. In the present study, we evaluate whether a novel ssODN design and down-regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 19 publications
3
41
0
Order By: Relevance
“…Deletion or down-regulation of the central MMR gene Msh2 dramatically improved the targeting frequency in mouse embryonic stem cells (ESCs) (7,8). Recently, this inhibitory effect of the MMR system has been confirmed in human hepatocytes (9), CHO-K1 cells (10) and HEK293T Lα cells (11). The involvement of the MMR system, which functions to correct replication errors that escape proofreading, provides an additional indication for ssODN-mediated gene targeting to take place during replication.…”
Section: Introductionmentioning
confidence: 86%
“…Deletion or down-regulation of the central MMR gene Msh2 dramatically improved the targeting frequency in mouse embryonic stem cells (ESCs) (7,8). Recently, this inhibitory effect of the MMR system has been confirmed in human hepatocytes (9), CHO-K1 cells (10) and HEK293T Lα cells (11). The involvement of the MMR system, which functions to correct replication errors that escape proofreading, provides an additional indication for ssODN-mediated gene targeting to take place during replication.…”
Section: Introductionmentioning
confidence: 86%
“…8 Nonetheless, full insight into the severity of unwanted mutagenesis has to await whole genome sequencing of ssODN-modified ESC. In other mammalian cell lines, such as mouse embryonic fibroblasts, 45 CHO-K1 cells 57 and mixed myoblast/fibroblast cultures, 58 transient downregulation of MSH2 by siRNA led to a twofold increased targeting frequency, whereas in human hepatocytes, stable knockdown of MSH2 increased the targeting frequency 20-to 35-fold. 59 In addition, inducible repression of hMLH1 resulted in a threefold increase in targeting frequency in a doxycycline-regulatable HEK293T La cell line.…”
Section: Temporary Mmr Suppression Allows Effective Gene Targetingmentioning
confidence: 99%
“…In this study, it was shown that gene correction by locked nucleic acid-protected ssODNs induced a similar accumulation of cells in G 2 as PTO-protected ssODNs. 57 On the other hand, Andrieu-Soler et al 61 reported that gene correction by locked nucleic acid-modified ssODNs did not preclude clonal expansion of the corrected cells. Other strategies were based on inhibition of the proliferating non-corrected cells by thymidine, 64 or monastrol, 65 to prevent dilution of the arrested corrected cells in the total population.…”
Section: Consequences Of Ssodn-mediated Gene Targeting On Cell Viabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…30,[41][42][43][44][45][46] Largely, mechanistic studies have utilized a mutated eGFP gene as the target and a functional eGFP is produced if the gene is repaired; then, the corrected cells express eGFP and display green fluorescence. In the standard model system, a single copy of the eGFP gene with a single base mutation -TAC → TAG -generating a stop codon has been stably integrated in the sequence of HCT116 cells.…”
Section: Recovery and Proliferation Of Genetically Modified Cancer Cellsmentioning
confidence: 99%